Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja Terhadap Kinerja Guru - Rumahorbo, Yanti (Jurnal Locus Penelitian dan Pengabdian, 2025)
The purpose of this research is to test the influence of work motivation and principals' leadership on teacher performance at SMA Negeri 2 Deiyai in Central Papua Province. This research applies survey methods and quantitative approaches, by collecting data from teachers who participated in the study by filling out questionnaires. Multiple linear regression is a data analysis method applied to determine the relationship between research variables. The research findings explain that the leadership of the principal has an influence on teacher performance, although it is not significant individually. On the other hand, work motivation has a significant influence on improving teacher performance. In addition, when the principal's leadership and work motivation are combined, they have a greater impact on the teacher's overall performance. Thus, improvements in the leadership aspect of school principals and increased teachers' work motivation can improve the quality of learning at school. Based on these findings, it is recommended that school principals be more proactive in creating a supportive work environment and giving appreciation to teachers for their performance. In addition, schools and other stakeholders must pay more attention to work motivation improvement programs to encourage more optimal performance of teachers.